Implicit motor learning in primary school children: A systematic review. Issue 22 (17th November 2021) - van Abswoude, Femke; Mombarg, Remo; de Groot, Wouter; Spruijtenburg, Gwennyth Eileen; Steenbergen, Bert
ABSTRACT: The aim of this study was to assess the current state of evidence and methodological quality of studies on implicit and explicit motor learning in both typically developing children and children with developmental disorders. A systematic literature review was conducted on the experimental literature published up to April 2020. A total of 25 studies were included. Studies were evaluated on methodological quality, paradigm used, and level of evidence. The results showed that implicit paradigms are as effective as explicit paradigms in both groups of children. Studies are predominantly experimental in nature involving mostly upper limb aiming tasks. The few studies that were performed outside the lab (n = 5) suggest superior efficacy of the implicit paradigm. Methodological quality varied between studies and was not always of sufficient standard to allow conclusions. In particular, manipulation checks were only performed in 13 studies (52% of all studies), limiting conclusions. Further progress can be made by focussing on improving methodological quality through retention testing by the inclusion of a control group, by the inclusion of a manipulation check, and via assessment of relevant co-variables, such as working memory, age, and motor competence.